Analisis respon peletakan vegetasi berdasarkan fungsi vegetasi terhadap kondisi tapak kawasan Kampus Unissula Semarang - Rahman, Boby (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019DO - 10.24843/JAL.2019.v05.i02.p12, 2019)
Analysis of vegetation laying response based on vegetation function against the site conditions of the Semarang Unissula campus area. Green open spaces become an inseparable part in all campus environments. No exception at the Sultan Agung Islamic University (Unissula) campus in Semarang with one of the concepts being Islamic, Green, Ecology and Smart (IGES). More than 1,600 vegetations are embedded in the campus area of Unissula. The purpose of this study is to review how far vegetation is able to support (provide environmental comfort) as a place for teaching, learning and all activity. By using qualitative methodology and superimpose map analysis techniques, an analysis of the function of vegetation that has been planted on the condition of the campus site of Unissula. The result is that the response of vegetation planting has adjusted to the condition of the site of the Unissula campus, this response is in the form of planting a vegetation function on noise, pollution, circulation and aesthetics. The analysis also shows that the area covered by vegetation canopy reaches 23% of the total area, but when viewed in more depth the distribution of land cover covered with vegetation canopy covers the pedestrian circulation of each unit (building function) to the mosque as The meeting point of this activity shows that vegetation planning is not only based on a scale of size but can also go through the approaches of areas that are places and patterns of movement of human activities.